Microencapsulação de Trichoderma spp. para o biocontrole de Macrophomina phaseolina (Tassi) Goid. em feijoeiro - Strahl, Marisa Ana (2022)
The demand for the use of products for sustainable agriculture, with a lower impact on the environment has been increasing. In this way, the biological control of diseases is an alternative to reduce the use of pesticides. Fungi of the genus Trichoderma spp. are an example of effective biological control against the pathogen Macrophomina phaseolina, the causal agent of gray stem rot, which affects several crops, including common bean. This soil-dwelling pathogen is difficult to control because it produces resistance structures that allow them to survive in the soil for a long period of time. However, the use of Trichoderma spp. as a biological control agent, it may encounter some problems, such as stress caused by biotic and abiotic factors. A possible solution to this type of problem is the use of microencapsulation techniques for biocontrol agents. Given the above, the objective of this work was to evaluate the action of Trichoderma spp. through the use of suspension and microencapsulated formulations from the lyophilization technique in the in vitro and in vivo biocontrol of Machophomina phaseolina and growth promotion in bean plants. For this purpose, four isolates of Trichoderma spp. were used, two from a commercial formulation based on Trichoderma harzianum, T. virens isolated from rhizospheric soil of common bean and T. asperellum isolated from rhizospheric soil of citrus orchards, and a phytopathogenic isolate from M. phaseolina. The antagonistic action of Trichoderma spp. in the form of suspension and microencapsulated formulation on M. phaseolina through the pairing of cultures and volatile metabolites in vitro. Afterwards, the isolates with lower mycelial growth rates were selected for follow-up of the in vivo studies. The isolates, with and without microencapsulated formulation, were used in seed treatment to evaluate plant growth promotion. To evaluate the control of the disease, the application of the microencapsulated formulation was carried out, as well as the suspension of the antagonists in the seed treatment, and the inoculation of the pathogen was carried out via substrate. Trichoderma spp. both in the form of suspension, as well as the microencapsulated formulation, were efficient in controlling the mycelial growth of M. phaseolina both in the pairing of cultures and by volatile metabolites. The application of Trichoderma spp., in vivo or microencapsulated formulation via seed treatment, was able to control the pathogen responsible for gray stem rot. The microencapsulated isolates showed a positive effect on root growth and leaf area. The microencapsulation technique did not interfere in the action of the antagonist in the biocontrol of M. phaseolina in the in vitro tests, as well as in the in vivo tests.